Multifocal ERG and Microperimetry Changes in Response to Ranibizumab Treatment of Neovascular AMD: Randomized Phase 2 Open-Label Study - Asahi MG (Dove Medical Press, 2020)
Masumi G Asahi, Josh Wallsh, Spencer M Onishi, Shari Kuroyama, Ron P Gallemore Clinical Research Department, Retina Macula Institute, Torrance, CA, USACorrespondence: Ron P Gallemore Tel +1 (310) 944-9393Fax +1 (310) 944-3393Email rongallemoremd@gmail.comPurpose: To compare monthly versus pro re nata (PRN) ranibizumab injections in the treatment of exudative macular degeneration (AMD) while assessing the utility of microperimetry (MP) and multifocal electroretinography (mfERG) testing when monitoring response to treatment.Methods: A randomized exploratory trial comparing the efficacy of monthly versus PRN dosing of ranibizumab (0.5 mg or 2.0 mg) for patients with exudative AMD over 12 months. High-resolution optical coherence tomography (HR-OCT) studies were used to guide PRN treatment and any cystic spaces or subretinal fluid prompted retreatment. Macular function was assessed using mean sensitivity on MP and N1-P1 response density on mfERG. Best-corrected visual acuity (BCVA) was measured with Early Treatment Diabetic Retinopathy Study (ETDRS) letters and anatomic response assessed with central foveal thickness (CFT) using HR-OCT studies.Results: The 12-month study was completed by 43 patients in the PRN cohort and 33 patients in the monthly cohort. Mean BCVA improved by 6.0 ± 1.3 ETDRS letters in the PRN cohort compared to 7.3 ± 2.8 ETDRS letters in the monthly cohort (p=0.68). A reduction in mean CFT of 64.5 ± 13.3 and 96.3 ± 22.0 μm occurred in the PRN and monthly cohorts, respectively (p=0.22). Macular function assessed with mfERG decreased comparably in both the PRN and monthly cohorts (p=0.33). For all patients, average mean sensitivity significantly improved by 1.7 ± 0.5 dB (p< 0.05) and N1-P1 response density significantly decreased by 0.52 ± 0.21 nV/deg2 (p< 0.05).Conclusion: Both PRN and monthly treatment of exudative AMD with ranibizumab improve visual function as assessed by BCVA and MP. Macular thickening also improved as demonstrated by HR-OCT findings. However, the decreased retinal function noted by mfERG suggests that some loss of retinal function still occurs despite effective treatment. These measures of visual function may be useful in assessing retinal health and response to treatment in future clinical trials.Keywords: age-related macular degeneration, microperimetry, multifocal ERG, ranibizumab